2004
DOI: 10.1023/b:biop.0000024288.82679.50
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine: A Suitable Nitrogen Source for Enhanced Shoot Multiplication in Cucumis sativus L.

Abstract: Shoot tip explants of cucumber (Cucumis sativus L. cv. Poinsett 76) were cultured in vitro on Murashige-Skoog medium with L-glutamine, ammonium nitrate, adenine sulphate, asparagine, ammonium succinate, potassium nitrate and sodium nitrate as the nitrogen sources along with optimal concentration of 0.044 mM benzyladenine to study their effects on in vitro morphogenesis. The explants grown with 0.068 mM L-glutamine displayed the highest culture response (74.6 %) and greatest shoot number per explant (13.6) at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 13 publications
7
33
0
3
Order By: Relevance
“…As easily accessible source of reduced nitrogen, it is generally more favorable than ammonium, to morphogenesis as reported for Cucumis sativus L. In the course of work done with the in vitro multiplication of Arachis hypogea L. from cotyledon explants, the presence of L-glutamine also improved and maintained high multiplication and growth rates. During transamination, glutamine transfers nitrogen to other carbohydrated substrates ( -keto acids) and the new amino acids immediately contribute to the biosynthesis of proteins [12,13]. The glutamine and glutamate byproduct are the primary sources of reduced nitrogen in the cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…As easily accessible source of reduced nitrogen, it is generally more favorable than ammonium, to morphogenesis as reported for Cucumis sativus L. In the course of work done with the in vitro multiplication of Arachis hypogea L. from cotyledon explants, the presence of L-glutamine also improved and maintained high multiplication and growth rates. During transamination, glutamine transfers nitrogen to other carbohydrated substrates ( -keto acids) and the new amino acids immediately contribute to the biosynthesis of proteins [12,13]. The glutamine and glutamate byproduct are the primary sources of reduced nitrogen in the cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports specify that reduced nitrogen forms, particularly amides and amino acids, can improve cell proliferation as well as regeneration in specific genotypes (Vasudevan et al, 2004).…”
mentioning
confidence: 99%
“…Thomas and Sreejesh (2004) have reported that the addition of 0.2 μM NAA with 4 μM 6-benzylaminopurine (BAP) was beneficial for adventitious shoot regeneration in the cotyledon-derived callus of ash gourd. When compared with cucumber (Vasudevan et al, 2004;Vasudevan et al, 2007b), watermelon (Sultana and Bari, 2003;Sultana et al, 2004), melon (Curuk et al, 2002;Muruganantham et al, 2002) and squash (Ananthakrishnan et al, 2003;Kathiravan et al, 2006), chieh-qua also needed a high concentration of 6-BA for shoot induction. Such a high concentration may influence shoot proliferation as well as elongation, and could be one of the reasons for the difficulty of regeneration of chieh-qua.…”
Section: Discussionmentioning
confidence: 99%